Tea and herbal infusions consumption in Portugal: consumer behaviors - Sousa, A. C.; Ribeiro, C.; Gonçalves, V. M. F.; Pádua, I.; Leal, S. (Scientific Letters, 2023)
Background: Tea and herbal infusions (THIs) consumption is recognized for its beneficial effects, which are attributed to the antioxidant properties of phenolic compounds [1–3].The wide diversity of THIs available in market and the absence or failure in quality control can expose the population to health risks [3]. Moreover, uncontrolled consumption may cause toxicity or lack of the expected benefits. Therefore, an understanding of the THIs consumption and consumer habits will allow adjustments in risk-benefit assessment for vulnerable population. Objective: The main aim was to understand THI consumption in Portugal. Methods: A web-based survey was developed and applied (January-February 2023), using Google forms® platform, after the Ethical Committee approval. Sociodemographic data, type of THIs consumed and brewing were collected. Descriptive statistics was performed using JASP 0.16.1.0. Results: A total of 720 participants completed the online survey, of which 47.2% declared drinking THIs ³2 cups/week (medium consumers) and 17.8% consumed ³2 cups/day (heavy consumers). In the latter, the majority were female (87.5%), of which 51.8% aged 40-60 years. In heavy THI consumers group, 10% were older than 61 years. Among the heavy and medium consumers, herbal Infusions, such as citronella (42.1%) and chamomile (35.7%), were most popular than green tea consumption (22.3%). For THI preparation, mostly of these consumers reported the use of tap water (82%) and bags (56%), but 41% reported the use either bags or leaves. Over 16% of heavy and medium consumers use more product quantity than recommended. Approximately 86% of the heavy and medium consumers indicated that, after boiling, let THIs rest for 5-10 minutes and, 78% removed bag/leave before drinking. Conclusions: Herbal infusions consumption was more frequent than green tea and heavy consumers were mainly older adults. This study contributes with relevant results for future risk–benefit assessments of THIs consumption available in the Portuguese market.